2022
DOI: 10.1371/journal.pone.0266253
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous discovery of novel task solutions in children

Abstract: Children often perform worse than adults on tasks that require focused attention. While this is commonly regarded as a sign of incomplete cognitive development, a broader attentional focus could also endow children with the ability to find novel solutions to a given task. To test this idea, we investigated children’s ability to discover and use novel aspects of the environment that allowed them to improve their decision-making strategy. Participants were given a simple choice task in which the possibility of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In comparison, a study investigating adults found high accuracy of the thigh-worn accelerometer for predicting time spent in each PA intensity category, as seen by sensitivities and specificities > 99% for correctly classifying each PA intensity category [ 68 ]. One possible explanation for the differences between children and adults could be the inconsistent performance of activities in children whereas adults could more consequently perform activities over a certain time period [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, a study investigating adults found high accuracy of the thigh-worn accelerometer for predicting time spent in each PA intensity category, as seen by sensitivities and specificities > 99% for correctly classifying each PA intensity category [ 68 ]. One possible explanation for the differences between children and adults could be the inconsistent performance of activities in children whereas adults could more consequently perform activities over a certain time period [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research on covariation-learning has shown that other procedures can be learned even in situations where the participants know the procedure that can solve the problem (Schuck et al, 2015 , 2022 ; Gaschler et al, 2019 ). These studies deal with situations in which participants are required to make a response corresponding to a stimulus with covariant two features.…”
Section: Discussionmentioning
confidence: 99%
“…This seems promising as Luo et al (2019) have summarized that reduction of ADHD symptoms over development correlates with the maturation of the prefrontal cortex and related circuitry. Based on reasoning about this maturation, Schuck et al (2022) have recently applied a covariation learning task to compare children and young adolescents. Strategy change was shown by 27.5% of the 8–10 year olds and by 28.2% of the adults.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to target this issue is to compare groups of persons potentially differing in task shielding. For instance, referring to differences in prefrontal cortex maturation among children and adolescents, Schuck et al (2022) tested for differences among children and young adults to deviate from instruction-based task performance. Children and young adults to a similar instead engaged in task-performance controlled by a stimulus feature that was not mentioned in the instructions, but was correlated with the instructed stimulus feature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation